2012
DOI: 10.1101/cshperspect.a011957
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Psychostimulant-Induced Structural Plasticity

Abstract: Psychostimulants robustly induce alterations in neuronal structural plasticity throughout brain reward circuits. However, despite our extensive understanding of how these circuits modulate motivated behavior, it is still unclear whether structural plasticity within these regions drives pathological behavioral responses in addiction. Although these structural changes have been subjected to an exhaustive phenomenological characterization, we still have a limited understanding of the molecular mechanisms regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 171 publications
(173 reference statements)
1
36
0
Order By: Relevance
“…Moreover, activation of CB1Rs in the NAc locally disinhibits dopamine release in this region (Cheer et al, 2004; Chen et al, 1993; Sperlágh et al, 2009) as does estradiol in the female NAc and caudate resulting in increased locomotor responses to psychostimulants (Becker and Rudick, 1999; Schultz et al, 2009; Thompson and Moss, 1994). Sustained enhancement of dopamine neurotransmission in the NAc and changes in MSN excitability are recognized as a key factors to the onset of drug addiction through structural remodeling of reward circuits leading to enhanced behavioral responses to psychostimulants (Golden and Russo, 2012; Kalivas and Duffy, 1990; Kourrich and Thomas, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, activation of CB1Rs in the NAc locally disinhibits dopamine release in this region (Cheer et al, 2004; Chen et al, 1993; Sperlágh et al, 2009) as does estradiol in the female NAc and caudate resulting in increased locomotor responses to psychostimulants (Becker and Rudick, 1999; Schultz et al, 2009; Thompson and Moss, 1994). Sustained enhancement of dopamine neurotransmission in the NAc and changes in MSN excitability are recognized as a key factors to the onset of drug addiction through structural remodeling of reward circuits leading to enhanced behavioral responses to psychostimulants (Golden and Russo, 2012; Kalivas and Duffy, 1990; Kourrich and Thomas, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Although initial studies indicated that repeated exposure to psychostimulants increased dendritic spine density within the NAc core (e.g., Li et al, 2004; Norrholm et al, 2003), more recent studies using advanced staining techniques and 3-D imaging, thought to more accurately represent neuroanatomical structure (Golden and Russo, 2012), have observed a decrease in spine density within this brain region following repeated cocaine administration (Dumitriu et al, 2012; Waselus et al, 2013). Independent of methodological issues, dendritic spine plasticity of MSNs in the NAc are associated with enhanced behavioral responsiveness to psychostimulants.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of psychostimulants on dendritic spines has been the focus of numerous studies(Golden and Russo 2012). The results of these studies suggest that patterns of dendritic spine plasticity depend on a number of factors, including route and context of drug administration, drug administration regime, and length of withdrawal after drug cessation (Golden and Russo 2012). However, what is particularly intriguing is that dendritic spine density in the NAc core is decreased 24 hours after repeated psychostimulant exposure (Dumitrui et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the specificity of the proteolytic response, we then used the pharmacologic inhibitor tPA serpin (Serpini1) (Galliciotti and Sonderegger, 2006). The elevated tPA activity in adult Lynx1 KO mice with MD was significantly decreased with tPA serpin in ex vivo V1 homogenates (Lynx1 KO MD, n ϭ 4; 0.61 Ϯ 0.079 vs Lynx1 KO ϩ tPA Serpin, n ϭ 4; 0.49 Ϯ 0.076, p Ͻ 0.05, paired Student's t test; Figure 1B).…”
Section: Tpa Activity Elevates In Adult V1 Following MD In Lynx1 Ko Micementioning
confidence: 99%